Electron Microscopy of Cracks in InxGa1-xAs/GaAs(001) Multi-Quantum Wells - Atici, Y.; Yildiz, K.; Akgul, U. (Polish Acad Sciences Inst Physics, 2015)
We studied cracks in two different InxGa1-xAs/GaAs(001) multi-quantum-well structures by electron microscopy. Transmission and scanning electron microscopy analyses of the sample-1 revealed that the epilayers associated with cracks. Detailed experimental works on the cracks were carried out by conventional and high-resolution electron microscopy. It was found that the epilayers were very effective on stopping the cracks in sample-1. Many dislocations were observed around the cracks and cracks tips. SEM images showed that the cracks formed an orthogonal set array accompanying with slits and pits. However, there were not observed any cracks in the sample-2.
Keywords: Heterostructures; Gaas; Defects; Stress; Growth; Films